A study of social media influences the intention and motivation for doing cosplay in Malaysia - Lee, Ming Jie (2023)
This study explores the influence of social media on the motivation of Malaysian cosplayers. It addresses a research gap by investigating how social media platforms like Facebook and Instagram have shaped the motivations and intentions of cosplayers to participant in this interest culture. This research seeks to understand how Malaysian cosplayers participant in cosplay have, whether it have connection with the raise of social media. To study this connection, 2 theories apply in this research which is Social Media Engagement Theory by Rebecca Dolan, J. C. (2015) and Motivation Theory by Edward L. Deci, R. J. (1991). The results of this research are trend to the social media have influence and provide a better entrance for the individual to study cosplay culture and participant into it, but there are answer that state the motivation that push the individual to have the intention continue cosplay is their self-interest